Community Perspectives on Social Influences on Suicide Within a Native American Reservation. (January 2022) - Cwik, Mary; Doty, S. Benjamin; Hinton, Alexandra; Goklish, Novalene; Ivanich, Jerreed; Hill, Kyle; Lee, Angelita; Tingey, Lauren; Craig, Mariddie
Relative to the general population, Native Americans (NA) bear a disproportionate burden of suicide-related mortality rates. NA males and females aged 15 to 24 years experience suicide rates nearly 3 times than the U.S. all races rates in this age group. Although efforts have been made to understand and reduce suicide in tribal communities, a large portion has focused on individual characteristics with less attention given to social factors that may also inform suicide. This article aims to build on a local conceptual model of NA youth suicide by examining additional potential social factors through qualitative interviews. Findings from the thematic analysis resulted in the identification of seven perceived social influences: contagion, violence and abuse, discrimination and bullying, negative expectations, spirituality, social support, and cultural strengths. Public health approaches to reduce suicide should consider local social factors that resonate with tribal communities to build resilience.